Asystole in 2 Pediatric Patients During Dexmedetomidine Infusion. (February 2023) - Lichtsinn, Katrin; Sehgal, Ila; Wilson, Alexandra
Introduction: Bradycardia is a known side effect of dexmedetomidine. Reports of sinus pauses or asystole, however, are rare. We present 2 cases of pediatric patients who developed asystole on a dexmedetomidine infusion. Summary of Cases: An 8-week-old male with RSV bronchiolitis and acute hypoxemic respiratory failure was started on dexmedetomidine for sedation at 0.2 mcg/kg/h with a maximum dose of 0.7mcg/kg/h. On Hospital day (HD) 4, on dexmedetomidine at 0.7 mcg/kg/h, he developed intermittent episodes of bradycardia with heart rates in the 60 s. Echocardiogram on HD 6 showed normal function. On HD 7, he began having periods of asystole lasting up to 6 seconds. Dexmedetomidine was discontinued, with the resolution of episodes of asystole after 6 hours. A 27-month-old male with a congenital left diaphragmatic hernia and pulmonary hypertension who had been weaned off sildenafil 6 months earlier underwent re-repair of left diaphragmatic hernia. Postoperatively he remained intubated and paralyzed. Dexmedetomidine was started at 0.3 mcg/kg/h for sedation, with a maximum dose of 1.2 mcg/kg/h. An echocardiogram on HD 3 showed good function with mild to moderate pulmonary hypertension. That evening, with dexmedetomidine at 1.1 mcg/kg/h, he developed a 15 second period of asystole requiring CPR. Dexmedetomidine was discontinued, and he was started on a midazolam infusion with no further episodes. Discussion: Both cases occurred in patients without cardiac conduction defects or on negative chronotropic or sympatholytic medications that have been associated with dexmedetomidine-induced asystole. We hypothesize that both episodes of asystole were due to increased patient-related vagal tone exacerbated by dexmedetomidine.